Turning unemployment into self-employment: Effectiveness and efficiency of two start-up programmes - Hans J. Baumgartner; Marco Caliendo (Institute for the Study of Labor (IZA), 2007)
Turning unemployment into self-employment has become a major focus of German active labour market policy (ALMP) in recent years. If effective, this would not only reduce Germany's persistently high unemployment rate, but also increase its notoriously low self-employment rate. Empirical evidence on the effectiveness of such programmes is scarce. The contribution of the present paper is twofold: first, we evaluate the effectiveness of two start-up programmes for the unemployed. Our outcome variables include the probability of being employed, the probability of being unemployed, and personal income. Second, based on the results of this analysis, we conduct an efficiency analysis, i.e., we estimate whether the Federal Employment Agency has saved money by placing unemployed individuals in these programmes. Our results show that at the end of the observation period, both programmes are effective and one is also efficient. The considerable positive effects present a stark contrast to findings from evaluations of other German ALMP programmes in recent years. Hence, ALMP programmes aimed at moving the unemployed into self-employment may prove to be among the most effective, both in Germany and elsewhere.
urn:nbn:de:101:1-20080415154
Keywords: 330; Arbeitslosigkeit; Arbeitsmarktpolitik; Selbstständige; Unternehmensgründung; Subvention; Wirkungsanalyse; Beschäftigungseffekt; Deutschland